Non Thermal Preservation Process of Apple Cider Based on Oscillating Magneting Field (OMF) Technology - Sari, Elok Kurnia Novita; Susilo, Bambang; Sumarlan, Sumardi Hadi (Jurnal Teknologi Pertanian, 2012)
Magnetic technology is one method of non thermal preservation for preserving food uses the magnetic field. Food preservation based on oscillating magnetic field technology, worked by using magnetic fields generated from currents to coils. The magnetic field is generated, then used to kill microorganism cells that are pathogen in food. The main purpose of this research is to design and study the characteristics and working principles of pasteurization machine based on oscillating magneting field, that tested to apple cider. Research methods used are experimental method by three treatment factors, namely the input voltage magnitude (V), the long treatment (t) and the input frecuency (f). The results of this study showed that the allocation of the magnetic field can safe the quality and keep the shelf life of aplle cider longer. At 130 V, frecuency at 50 Hz for 25 minutes treatment time, the total of microorganisms decreased up to 99.96%, and the last microorganisms are 10 col/g. Moreover, the degree of acidity (pH) and total suspended solid of apple cider more stable and has shelf life longer than the others. Food preservation technologies by providing a magnetic field does not cause high heat, so no loss of nutrients and damage to the material. So that the preservation process with this technology can be applied to food preservation process. Keywords: non thermal preservation, pasteurization, magnetic technology, pathogen microbial